Translational Concepts of mGluR5 in Synaptic Diseases of the Brain - Piers, Thomas M.; Kim, Dong Hyun; Kim, Byeong C.; Regan, Philip; Whitcomb, Daniel J.; Cho, Kwangwook (Frontiers in Pharmacology, 2012)
The G-protein coupled receptor family of glutamate receptors, termed metabotropic glutamate receptors (mGluRs), are implicated in numerous cellular mechanisms ranging from neural development to the processing of cognitive, sensory, and motor information. Over the last decade, multiple mGluR-related signal cascades have been identified at excitatory synapses, indicating their potential roles in various forms of synaptic function and dysfunction. This review highlights recent studies investigating mGluR5, a subtype of group I mGluRs, and its association with a number of developmental, psychiatric and senile synaptic disorders with respect to associated synaptic proteins, with an emphasis on translational pre-clinical studies targeting mGluR5 in a range of synaptic diseases of the brain.